RESEARCH ON IMPROVED 6A-12M SCREW CONVEYOR PILES (International conference on multidisciplinary science, 2025)
The article presents the results of research conducted on the 6A-12M equipment with improved screw conveyor piles. The research was carried out in the equipment for removing small impurities installed at the Rishton cotton ginning enterprise. In the technological process, an improved version of the screw conveyor was installed in the lower row of the 1st section of the 2nd 6A-12M cleaning equipment. It is possible to make a comparison on the whole equipment or on sections. According to the results of the research, it was found that the efficiency of cleaning from small impurities is 6% higher than the existing version of the 6A-12M equipment.